تصور مقترح لتدريس مادة العلوم في المرحلة الإبتدائية باستخدام الدرما الإبداعية العلوم ‏لتلاميذ المرحلة الإبتدائية في المملكة العربية السعودية من وجهة نظر المعلمين - بلخي، إبتسام عبد السلام عبد الله (Kulliyah of Education, International Islamic University Malaysia, 2018)
This study aims to identify the importance of professional development of teaching methods ‎between male and female teachers in the Sabya city, Jizan region, Kingdom of Saudi Arabia ‎‎(KSA). The study was conducted in three primary schools, on the third grades (Grade 3) ‎classes, and on the science textbooks for the first semester. The study conducted on nine ‎participants (9); in which six are female teachers (6), and three are male teachers (3). This ‎study aims to identify the importance of professional development of teaching methods ‎between teachers and teachers in the Kingdom of Saudi Arabia. The study was conducted in ‎three primary schools; on the third grade was the science course for the first semester. The ‎study consisted of (9) participants, six teachers (6) females, and three (3) male teachers. The ‎researcher uses the qualitative research methodology, which based on data collection ‎through the personal interview with the participants, and the classroom observation in the ‎three female teachers' classrooms. The researcher also analyses and studies the data to get ‎an in-depth and detailed results that for the role of teachers in the development of teaching ‎methodologies in the Kingdom of Saudi Arabia. The study found that the teachers observe ‎the effectiveness and importance of applying the method of creative drama in teaching ‎science curriculum in Saudi Arabia, especially as it is a new method that connects between ‎the theoretical and practical aspects. However, in order to be able to do so, the intensity of ‎the curriculum must be addressed, the number of pupils per classroom should also be ‎reduced, and the school facilities should be provided with an increase in the number of ‎lesson periods. The Teachers also see the effective role of teaching by using creative drama, ‎which can contribute to the development of knowledge and information of students, and the ‎teachers see it as a new teaching and strategy that already works to develop the tendencies ‎and attitudes of students, and to identify the talents of students and the development of ‎social values and eliminate the Psychological problems of some students, as It is one of the ‎new teaching methodologies that the teacher can adopt as a teaching methodology in the ‎classroom for students. Because it is an active collaborative learning that linked between the ‎theoretical and practical aspects, which is the basis of the educational process, especially in ‎the primary levels. ‎